KATA SAPAAN BAHASA MELAYU JAMBI DI DESA TELUK RENDAH ILIR KECAMATAN TEBO ILIR KABUPATEN TEBO - Fithriani, Zulpa (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
The purpose of this study is to produce the form and use of kinship and non-kinship terms in Jambi Malay language in the village of Teluk Rendah Ilir Tebo Ilir District Tebo District. The method used in this research is descriptive method. With a qualitative approach involving the language community is directed at the background and the individual concerned as a unified whole. Data collection in this research that is through observation, that is by participant observation as inner observation process conducted by researcher to collect data through informant-informant. The method used in data collection is the method of referring and the method of ably. Data analysis using extralingual method to analyze the form of the appropriate or reasonable speech to be used to the person in the context and situation of certain words, the data obtained is studied with a sociolinguistic approach. To test the validity of research data is done by triangulation technique, that is compare the theory and data obtained. The results of this study indicate that the greetings in Jambi Malay language in the village of Teluk Rendah Ilir Tebo Ilir subdistrict Tebo District consists of: (1) greeting word horizontal [0] (sibling, cousin, wife between wife, and antaripar), vertical up [+1] (Father / Mother) and [+2] (Grandpa / grandmother), vertical down [-1] (child) and [-2] (grandchild), (2) greeting non-kinship words in the general public, non-kinship in religion, non-friendship greeting in profession / position, and non-kinship greeting in adat. For the use of the word greeting in Jambi Malay in Lower Bay Village Ilir Tebo Ilir District Tebo Regency is adapted to the context and situation in the language event between speakers, speakers, and people spoken outside speakers and speakers.